The Effect Of Servıce Qualıty On The Satısfactıon Level: A Case Study In Mersın Provınce - Yusuf Er (Selcuk University, 2020)
This study seeks to investigate to determine the differentiation situations according to some demographic variables of the individuals who are engaged in recreational activities in Mersin for a healthy life in an attempt to reveal the effect of the service quality on the satisfaction level. The sample group of the study was determined via convenience sampling method, and individuals preferring recreational activities in Mersin were chosen on a voluntary basis. A total of 424 participants, 158 female (37.3%) and 266 male (62.7%), participated in the study. The questionnaire form was used to collect research data and the scale of "Service Quality and Customer Satisfaction" consisting of 38 questions developed by Süllüoğlu was used to measure the service and satisfaction levels of the participants when being engaged in recreational activities [18]. In the analysis of the data obtained in the study, the percentage and frequency were used to determine the distribution of the personal information of the participants, while the skewness and kurtosis values of the data were checked to determine whether the data showed a normal distribution. The analysis revealed that the data has a normal distribution. In addition to descriptive statistical models, t-test and Anova analysis methods were used in the statistical analysis of data (α = 0.05). As a result, significant differences were found in sub-dimensions regarding the service quality and satisfaction levels of the participants according to variables including gender, level of welfare, and the frequency of use at the facility.